Laparoscopic retrieval of an intra-abdominal air gun pellet. (14th May 2015) - Oliphant, Zoe; Tudor, Edward; Bamford, Richard; Mahon, David
Abstract : A 19-year-old man presented to the emergency department following an air gun pellet injury to the abdomen. He was clinically stable and underwent laparoscopic retrieval of the pellet, which was found embedded in the small bowel mesentery. He recovered fully and was discharged after 2 days. We further discuss air gun-related injuries.